Organic composite phenolic resin material and preparation method thereof
By introducing cashew phenol and boric acid into the phenolic resin and compounding it with polyether etherketone fiber and modified graphene oxide, the problem of insufficient thermal stability and mechanical properties of traditional phenolic resins is solved, and higher thermal stability and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411938851.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
The thermal stability and mechanical properties of traditional phenolic resins are insufficient, making it difficult to meet the needs of industrial production.
The thermal stability and mechanical properties of the phenolic resin are enhanced by introducing cashew phenol and boric acid and compounding with polyether etherketone fibers and modified graphene oxide.
The thermal stability and flexibility of the phenolic resin are significantly improved and its mechanical properties are enhanced, making it more suitable for industrial applications.
Smart Images

Figure BDA0005212132420000081 
Figure BDA0005212132420000091
Abstract
Description
Technical Field
[0001] The present application relates to the field of phenolic resins, and in particular to an organic composite phenolic resin material and a preparation method thereof. Background Art
[0002] Phenolic resin is a polymer compound formed by the condensation reaction of phenol and formaldehyde molecules under the catalysis of acid or base. It is widely used in industry.
[0003] With the development of industry, the performance requirements for phenolic resins are constantly increasing. However, traditional phenolic resins usually have poor resistance and are difficult to meet the needs of industrial production, so there is room for improvement. Summary of the invention
[0004] In order to improve the thermal stability of phenolic resin, the present application provides an organic composite phenolic resin material and a preparation method thereof.
[0005] The present application provides an organic composite phenolic resin material and a preparation method thereof using the following technical solutions: In the first aspect, the present application provides an organic composite phenolic resin material, which adopts the following technical solution: An organic composite phenolic resin material comprises the following components by weight: 120-140 parts of modified phenolic resin matrix, 12-20 parts of modified fiber, 8-18 parts of curing agent; The modified phenolic resin raw materials include phenol, oxalic acid, boric acid, formaldehyde and cardanol.
[0006] By adopting the above technical scheme, cardanol, a green natural phenol, is introduced into the phenolic resin matrix. After reacting with formaldehyde, cardanol has the flexibility of aliphatic compounds, thereby improving the flexibility and thermal stability of the phenolic resin and making the preparation of the phenolic resin more green and environmentally friendly; at the same time, boric acid is introduced into the resin to improve the reaction activity, and can synergistically improve the thermal stability of the resin matrix with cardanol.
[0007] Preferably, the modified phenolic resin matrix is prepared by the following method: Phenol, boric acid, cardanol and formaldehyde are mixed, oxalic acid is added and stirred, the temperature is increased for reaction, and a modified phenolic resin matrix is obtained after dehydration.
[0008] By adopting the above technical scheme, boric acid can play a certain catalytic role, and the hydroxyl group in the boric acid can also participate in the reaction to form a boron ester bond with the hydroxyl group or hydroxymethyl group in phenol, thereby generating a branched structure, improving the softening point of the phenolic resin, and allowing cardanol to be further introduced, so that the thermal stability of the prepared phenolic resin is improved and the toughness is also improved.
[0009] Preferably, the mass ratio of boric acid to cardanol is 1:(33-37).
[0010] By adopting the above technical solution, preferably the mass ratio between boric acid and cardanol is within the above range, the stability of the prepared modified phenolic resin matrix can be further improved.
[0011] Preferably, the polyetheretherketone fiber composite material comprises silane-modified polyetheretherketone fiber and modified graphene oxide.
[0012] By adopting the above technical solution, after adding silane-modified polyetheretherketone fiber and modified graphene oxide to the phenolic resin, the overall thermal stability of the phenolic resin can be further improved, and the overall mechanical properties of the phenolic resin matrix can be improved.
[0013] Preferably, the silane-modified polyetheretherketone fiber is prepared by the following method: The polyetheretherketone fiber is mixed with acetone to remove impurities on the surface of the polyetheretherketone fiber, and after drying, it is mixed with nitric acid and sulfuric acid, stirred and washed to neutrality, and then dried, and then mixed with stannous chloride and hydrochloric acid, stirred and dried to obtain pretreated polyetheretherketone fiber; silane coupling agent, ethanol and water are mixed to obtain a silane coupling agent solution, and the pretreated polyetheretherketone fiber is immersed in the silane coupling agent solution, and dried after immersion to obtain silane-modified polyetheretherketone fiber. By adopting the above technical scheme, amino groups are introduced into the surface of the polyetheretherketone fiber after surface treatment. The compatibility of polyetheretherketone fiber is improved, and it can be more stable in the resin system. The surface of the polyetheretherketone fiber is treated with a silane coupling agent to improve the roughness of the surface of the polyetheretherketone fiber, and the phenolic resin can be more stable in the system. At the same time, the introduction of the silane coupling agent can form bonds with the interfaces of other components in the phenolic resin system, further promoting the stability of the polyetheretherketone fiber. The friction resistance of the polyetheretherketone fiber after silane treatment is further improved, and the mechanical strength of the phenolic resin system can be improved.
[0014] Preferably, the mass ratio between the polyetheretherketone fiber and the silane coupling agent is 1:(0.08-0.12).
[0015] By adopting the above technical solution, preferably the mass ratio between the polyetheretherketone fiber and the silane coupling agent is within the above range, which can further improve the overall stability of the silane-modified polyetheretherketone fiber.
[0016] Preferably, the modified graphene oxide comprises graphene oxide and m-phenylenediamine.
[0017] Preferably, the modified graphene oxide is prepared by the following method: The graphene oxide and m-phenylenediamine are dispersed and mixed with deionized water, and stirred for reaction after ultrasonic treatment. After the reaction, the mixture is filtered and freeze-dried to obtain the modified graphene oxide.
[0018] By adopting the above technical solution, after the amino group of m-phenylenediamine reacts with the epoxy group of graphene oxide, the spacing between graphene oxide flakes is increased, so that the graphene oxide can be dispersed more evenly in the phenolic resin system, thereby improving the overall stability of the phenolic resin system. At the same time, m-phenylenediamine is bonded to the phenolic resin, which further improves the compatibility between graphene oxide and the phenolic resin, thereby improving the overall stability of the system.
[0019] Preferably, the mass ratio between the silane-modified polyetheretherketone fiber and the modified graphene oxide is (4.2-4.6):1.
[0020] By adopting the above technical solution, preferably the mass ratio between the silane-modified polyetheretherketone fiber and the modified graphene oxide is within the above range, which can further improve the overall stability of the prepared polyetheretherketone fiber composite material.
[0021] In a second aspect, the present application provides a method for preparing an organic composite phenolic resin material, which adopts the following technical scheme: A method for preparing an organic composite phenolic resin material comprises the following steps: The modified phenolic resin matrix and the polyetheretherketone fiber composite material are mixed, and a curing agent is added after stirring, and the stirring is continued, and then the mixture is cured to obtain an organic composite phenolic resin material.
[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. By introducing cardanol into the phenolic resin system, the stability and flexibility of the phenolic resin can be improved, and the thermal stability of the phenolic resin system can be further improved. After adding boric acid to the system, the reaction activity can be further improved, and the thermal stability of the phenolic resin can be improved together with cardanol. 2. Silane-modified polyetheretherketone fiber and modified graphene oxide are also added to the system. The combination of the two can synergistically improve the overall mechanical properties of the resin system and further improve the thermal stability of the resin system; 3. The roughness of the surface of the polyetheretherketone fiber treated with the silane coupling agent is improved, so that the polyetheretherketone fiber can be more stably dispersed in the phenolic resin system, thereby making the phenolic resin system more stable; after the graphene oxide is modified with m-phenylenediamine, the graphene oxide can be more evenly dispersed in the resin system and can be bonded with the resin system, thereby improving the stability and mechanical properties of the resin system. DETAILED DESCRIPTION
[0023] The present application is further described in detail below with reference to the embodiments: Description of raw materials: All raw materials in the examples are commercially available; the silane coupling agent is γ-aminopropyltriethoxysilane (CAS No.: 919-30-2); and the curing agent is paraformaldehyde (CAS No.: 30525-89-4).
[0024] Example 1 Preparation of modified graphene oxide: 10 g of graphene oxide and 76 g of m-phenylenediamine (CAS No.: 108-45-2) were dispersed in 5 L of deionized water, ultrasonically treated for 40 min, and then stirred for reaction in a 95 ° C oil bath for 5.5 h. After the reaction was completed, it was filtered and re-added to 95 ° C deionized water, and filtered again. After repeated filtration for 3 times, the product was freeze-dried in a freeze drying oven at a temperature of -20 ° C for 36 h to obtain modified graphene oxide.
[0025] Preparation of silane-modified polyetheretherketone fibers: 46.3 g of polyetheretherketone fiber was cut into fibers of about 3 cm in length, the cut polyetheretherketone fiber was completely immersed in 500 g of acetone, soaked for 12 hours, surface impurities were removed, and the fiber was dried at 50°C for 6 hours, nitric acid and sulfuric acid were mixed in a volume ratio of 8:1 to obtain a mixed solution, the dried polyetheretherketone fiber was immersed in the mixed solution, stirred for 3 minutes, and then washed with deionized water until neutral, the polyetheretherketone fiber was dried at 50°C in a nitrogen-protected environment, stannous chloride and hydrochloric acid were mixed in a mass ratio of 1:5 to obtain a stannous chloride mixed solution, and the dried fiber after secondary drying was added. The dried polyetheretherketone fiber is added to the stannous chloride mixed solution, stirred at 70°C for 24 hours, and then transferred to a vacuum drying oven and dried at 70°C for 24 hours to obtain the pretreated polyetheretherketone fiber. 3.7g of silane coupling agent, 90g of deionized water and 10g of anhydrous ethanol are mixed to obtain a silane coupling agent solution. The pretreated polyetheretherketone fiber is mixed with the silane coupling agent solution so that the pretreated polyetheretherketone fiber is completely soaked in the silane coupling agent solution. After soaking for 3g, the polyetheretherketone fiber is treated in an oven at 90°C for 12 hours to obtain silane-modified polyetheretherketone fiber.
[0026] Preparation of polyetheretherketone fiber composites: 7.69 g of modified graphene oxide was added to 200 g of N,N-dimethylformamide, and the modified graphene oxide dispersion was obtained after ultrasonic dispersion for 30 minutes. 32.31 g of silane-modified polyetheretherketone fiber was added to the modified graphene oxide dispersion, and stirred for 6 hours under nitrogen protection and 50°C atmosphere. Then the solvent was removed and the mixture was dried in an oven at 70°C for 12 hours to obtain a polyetheretherketone fiber composite material.
[0027] Preparation of modified phenolic resin matrix: 100 g of phenol, 0.61 g of boric acid, 20 g of cardanol (CAS No.: 501-24-6) and 500 g of a 37% formaldehyde solution were mixed, 1 g of oxalic acid (CAS No.: 144-62-7) was added, stirred for 30 min, heated to 100 ° C, refluxed for 2 h, and dehydrated to obtain a modified phenolic resin matrix.
[0028] Preparation of organic composite phenolic resin materials: 120 g of modified phenolic resin matrix and 12 g of polyetheretherketone fiber composite material were mixed, stirred at a speed of 300 r / min for 4 hours, 8 g of curing agent was added, stirred at a speed of 200 r / min for 30 minutes, then transferred to a vacuum drying oven, and cured at 150°C for 4 hours to obtain an organic composite phenolic resin material.
[0029] Example 2 Preparation of modified graphene oxide: 10 g of graphene oxide and 88 g of m-phenylenediamine were dispersed in 5 L of deionized water, ultrasonically treated for 40 min, and then stirred in a 95 °C oil bath for 5.5 h. After the reaction was completed, the mixture was filtered and re-added to 95 °C deionized water, filtered again, and after repeated filtration for 3 times, the product was freeze-dried in a freeze drying oven at -20 °C for 36 h to obtain modified graphene oxide.
[0030] Preparation of silane-modified polyetheretherketone fibers: 44.64 g of polyetheretherketone fiber was cut into fibers of about 3 cm in length, the cut polyetheretherketone fiber was completely immersed in 500 g of acetone, soaked for 12 hours, surface impurities were removed, and the fiber was dried at 50°C for 6 hours, nitric acid and sulfuric acid were mixed in a volume ratio of 8:1 to obtain a mixed solution, the dried polyetheretherketone fiber was immersed in the mixed solution, stirred for 3 minutes, and then washed with deionized water until neutral, the polyetheretherketone fiber was dried at 50°C in a nitrogen-protected environment, stannous chloride and hydrochloric acid were mixed in a mass ratio of 1:5 to obtain a stannous chloride mixed solution, and the dried fiber after secondary drying was added. The dried polyetheretherketone fiber is added to the stannous chloride mixed solution, stirred at 70°C for 24h, and then transferred to a vacuum drying oven and dried at 70°C for 24h to obtain the pretreated polyetheretherketone fiber. 5.36g of silane coupling agent, 90g of deionized water and 10g of anhydrous ethanol are mixed to obtain a silane coupling agent solution. The pretreated polyetheretherketone fiber is mixed with the silane coupling agent solution so that the pretreated polyetheretherketone fiber is completely soaked in the silane coupling agent solution. After soaking for 3g, the polyetheretherketone fiber is treated in an oven at 90°C for 12h to obtain a silane-modified polyetheretherketone fiber.
[0031] Preparation of polyetheretherketone fiber composites: 7.14 g of modified graphene oxide was added to 200 g of N,N-dimethylformamide, and the modified graphene oxide dispersion was obtained after ultrasonic dispersion for 30 minutes. 32.86 g of silane-modified polyetheretherketone fiber was added to the modified graphene oxide dispersion, and stirred for 6 hours under nitrogen protection and 50°C atmosphere. Then the solvent was removed and the mixture was dried in an oven at 70°C for 12 hours to obtain a polyetheretherketone fiber composite material.
[0032] Preparation of modified phenolic resin matrix: 100 g of phenol, 0.54 g of boric acid, 20 g of cardanol and 500 g of 37% formaldehyde solution were mixed, 1 g of oxalic acid was added, stirred for 30 min, heated to 100° C., refluxed for 2 h, and dehydrated to obtain a modified phenolic resin matrix.
[0033] Preparation of organic composite phenolic resin materials: 140 g of modified phenolic resin matrix and 20 g of polyetheretherketone fiber composite material were mixed, stirred at a speed of 300 r / min for 4 hours, 18 g of curing agent was added, stirred at a speed of 200 r / min for 30 minutes, then transferred to a vacuum drying oven, and cured at 150°C for 4 hours to obtain an organic composite phenolic resin material.
[0034] Example 3 Preparation of modified graphene oxide: 10 g of graphene oxide and 82 g of m-phenylenediamine were dispersed in 5 L of deionized water, ultrasonically treated for 40 min, and then stirred in a 95 °C oil bath for 5.5 h. After the reaction was completed, the mixture was filtered and re-added to 95 °C deionized water, filtered again, and after repeated filtration for 3 times, the product was freeze-dried in a freeze drying oven at -20 °C for 36 h to obtain modified graphene oxide.
[0035] Preparation of silane-modified polyetheretherketone fibers: 45.45 g of polyetheretherketone fiber was cut into fibers of about 3 cm in length, the cut polyetheretherketone fiber was completely immersed in 500 g of acetone, soaked for 12 hours, surface impurities were removed, and the fiber was dried at 50°C for 6 hours, nitric acid and sulfuric acid were mixed in a volume ratio of 8:1 to obtain a mixed solution, the dried polyetheretherketone fiber was immersed in the mixed solution, stirred for 3 minutes, and then washed with deionized water until neutral, the polyetheretherketone fiber was dried at 50°C in a nitrogen-protected environment, stannous chloride and hydrochloric acid were mixed in a mass ratio of 1:5 to obtain a stannous chloride mixed solution, and the dried fiber after secondary drying was added. The dried polyetheretherketone fiber is added to the stannous chloride mixed solution, stirred at 70°C for 24 hours, and then transferred to a vacuum drying oven and dried at 70°C for 24 hours to obtain the pretreated polyetheretherketone fiber. 4.55g of silane coupling agent, 90g of deionized water and 10g of anhydrous ethanol are mixed to obtain a silane coupling agent solution. The pretreated polyetheretherketone fiber is mixed with the silane coupling agent solution so that the pretreated polyetheretherketone fiber is completely soaked in the silane coupling agent solution. After soaking for 3g, the polyetheretherketone fiber is treated in an oven at 90°C for 12 hours to obtain a silane-modified polyetheretherketone fiber.
[0036] Preparation of polyetheretherketone fiber composites: 7.41 g of modified graphene oxide was added to 200 g of N,N-dimethylformamide, and the modified graphene oxide dispersion was obtained after ultrasonic dispersion for 30 minutes. 32.59 g of silane-modified polyetheretherketone fiber was added to the modified graphene oxide dispersion, and stirred for 6 hours under nitrogen protection and 50°C atmosphere. Then the solvent was removed and the mixture was dried in an oven at 70°C for 12 hours to obtain a polyetheretherketone fiber composite material.
[0037] Preparation of modified phenolic resin matrix: 100 g of phenol, 0.57 g of boric acid, 20 g of cardanol and 500 g of 37% formaldehyde solution were mixed, 1 g of oxalic acid was added, stirred for 30 min, heated to 100° C., refluxed for 2 h, and dehydrated to obtain a modified phenolic resin matrix.
[0038] Preparation of organic composite phenolic resin materials: 130 g of modified phenolic resin matrix and 16 g of polyetheretherketone fiber composite material were mixed, stirred at a speed of 300 r / min for 4 hours, 13 g of curing agent was added, stirred at a speed of 200 r / min for 30 minutes, then transferred to a vacuum drying oven, and cured at 150°C for 4 hours to obtain an organic composite phenolic resin material.
[0039] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, when preparing silane-modified polyetheretherketone fiber, 47.62 g of polyetheretherketone fiber and 2.38 g of silane coupling agent are used.
[0040] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, when preparing silane-modified polyetheretherketone fiber, 43.48 g of polyetheretherketone fiber and 6.52 g of silane coupling agent are used.
[0041] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, the mixed solution and the stannous chloride mixed solution are not used to treat the polyetheretherketone fiber.
[0042] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, 60 g of m-phenylenediamine is used when preparing modified graphene oxide.
[0043] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 3, 100 g of m-phenylenediamine is used when preparing modified graphene oxide.
[0044] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the polyetheretherketone composite fiber component, 31.84 g of silane-modified polyetheretherketone fiber and 8.16 g of modified graphene oxide are used.
[0045] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, when preparing the polyetheretherketone composite fiber component, 33.21 g of silane-modified polyetheretherketone fiber and 6.79 g of modified graphene oxide are used.
[0046] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, when preparing the polyetheretherketone composite fiber component, the modified graphene oxide is replaced by ordinary graphene oxide.
[0047] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, when preparing the polyetheretherketone composite fiber component, only the modified graphene oxide and the silane-modified polyetheretherketone fiber are physically mixed.
[0048] Embodiment 13 Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that in Example 13, 0.67 g of boric acid is used when preparing the modified phenolic resin matrix.
[0049] Embodiment 14 Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that in Example 14, 0.5 g of boric acid is used when preparing the modified phenolic resin matrix.
[0050] Comparative Example 1 Comparative Example 1 is based on Example 3. The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, cardanol is not added when preparing the modified phenolic resin matrix.
[0051] Comparative Example 2 Comparative Example 2 is based on Example 3. The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, no boric acid is added when preparing the modified phenolic resin matrix.
[0052] Comparative Example 3 Comparative Example 3 is based on Example 3. The difference between Comparative Example 3 and Example 3 is that in Comparative Example 3, no modified graphene oxide is added to the polyetheretherketone composite fiber component.
[0053] Performance testing The samples of Examples 1-14 and Comparative Examples 1-3 were sampled and the following performance tests were performed: (1) Thermal stability test A synchronous thermal analyzer (instrument model: STA449F5) was used for thermogravimetric analysis (TG). Each sample was tested three times, the average value was taken, and the test results were filled in Table 1. The test indicators are as follows: test temperature range: 200-1000°C; heating rate: 30K / min; test atmosphere: nitrogen atmosphere.
[0054] (2) Mechanical properties test The impact strength of the samples was tested according to GB / T2567-2008. Each sample was tested 3 times, and the average value was taken. The test results were filled in Table 1.
[0055] Table 1 Performance test results of samples of Examples 1-14 and Comparative Examples 1-3 Data analysis Combined with Table 1, it can be seen that the initial thermal decomposition temperatures of Examples 1-3 are all above 400°C, and the residual carbon rates at 1000°C are all above 75%, indicating that the phenolic resin prepared in this application has good thermal stability; the impact strength of Examples 1-3 is all above 3 kJ / m 2 The above indicates that the phenolic resin prepared in the present application has good impact resistance.
[0056] In Example 4 and Example 5, when preparing silane-modified polyetheretherketone fiber, the mass ratio between the polyetheretherketone fiber and the silane coupling agent is not within the range specified in the present application. When the content of the silane coupling agent is too little, the effect of improving the surface roughness of the polyetheretherketone fiber is difficult to be further improved, and the compatibility of polyetheretherketone in the resin is reduced, and the stability is reduced. When the content of the silane coupling agent is too much, the surface of the polyetheretherketone fiber is too rough, and too many holes affect the overall stability of the polyetheretherketone fiber, causing the performance of the polyetheretherketone fiber composite material to decline.
[0057] In Example 6, the mixed liquid and the stannous chloride mixed liquid were not used to treat the surface of the polyetheretherketone fiber. The surface of the polyetheretherketone that has not been pretreated contains impurities, which reduces the treatment effect of the silane coupling agent on the surface of the polyetheretherketone fiber, affecting the improvement effect of the surface roughness of the polyetheretherketone fiber.
[0058] In Example 7 and Example 8, when preparing modified graphene oxide, the mass ratio of m-phenylenediamine to graphene oxide is not within the range specified in the present application. When the content of m-phenylenediamine is too low, the improvement effect of increasing the distance between graphene oxide sheets decreases, causing graphene oxide to agglomerate in the system, affecting the stability of the system. When the content of m-phenylenediamine is too high, the overall stability of the modified graphene oxide will also decrease.
[0059] In Examples 9 and 10, when preparing the polyetheretherketone composite fiber components, the mass ratio between the silane-modified polyetheretherketone fiber and the modified graphene oxide is not within the range specified in the present application. When the content of modified graphene oxide is too much, the graphene oxide will agglomerate in the system, affecting the overall stability of the system. When the content of modified graphene oxide is too little, it is difficult to form a continuous pathway with the silane-modified polyetheretherketone fiber, resulting in a decrease in thermal stability and difficulty in further improving the mechanical properties of the component.
[0060] In Example 11, ordinary graphene oxide is used when preparing the polyetheretherketone composite fiber component. The unmodified graphene oxide agglomerates in the system, affecting the overall stability of the system. At the same time, it is difficult to improve the compatibility of graphene oxide in the system, and the interface bonding performance is reduced.
[0061] In Example 12, the modified graphene oxide and the silane-modified polyetheretherketone fiber were only physically mixed, and the bonding performance between the graphene oxide and the polyetheretherketone fiber was reduced, making it difficult to form a stable connection system, resulting in a reduction in the overall performance of the resin system.
[0062] In Example 13 and Example 14, when preparing the modified phenolic resin matrix, the mass ratio of boric acid to cardanol is not within the range specified in the present application. When the boric acid content is too low, the viscosity and softening point of the resin system are difficult to improve, and it is difficult to further promote the bonding between cardanol and the resin system; when the boric acid content is too high, the viscosity of the phenolic resin system is too high, the stability is reduced, and the bonding performance between the components in the resin system and the resin system is reduced, affecting the overall performance of the resin system.
[0063] In Comparative Example 1, no cardanol was added, so it was difficult to further improve the thermal stability of the resin system, and it was also difficult to further improve the mechanical properties.
[0064] In Comparative Example 2, no boric acid is added, and the viscosity and softening point of the resin system are difficult to improve, making it difficult to further improve the mechanical properties of the resin system and to promote the bonding between cardanol and the resin system.
[0065] In Comparative Example 3, no modified graphene oxide is added, because the mechanical properties and thermal stability of the component to which modified graphene oxide is added are difficult to be further improved.
[0066] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. An organic composite phenolic resin material, characterized in that: The composition includes the following components by mass: 120-140 parts of modified phenolic resin matrix, 12-20 parts of modified fiber, 8-18 parts of curing agent; The modified phenolic resin raw materials include phenol, oxalic acid, boric acid, formaldehyde and cardanol.
2. The organic composite phenolic resin material according to claim 1, characterized in that: The modified phenolic resin matrix is prepared by the following method: Phenol, boric acid, cardanol and formaldehyde are mixed, oxalic acid is added and stirred, the temperature is increased for reaction, and a modified phenolic resin matrix is obtained after dehydration.
3. The organic composite phenolic resin material according to claim 2, characterized in that: The mass ratio between the boric acid and cardanol is 1:(33-37).
4. The organic composite phenolic resin material according to claim 1, characterized in that: The polyetheretherketone fiber composite material comprises silane-modified polyetheretherketone fiber and modified graphene oxide.
5. The organic composite phenolic resin material according to claim 4, characterized in that: The silane-modified polyetheretherketone fiber is prepared by the following method: The polyetheretherketone fiber is mixed with acetone to remove impurities on the surface of the polyetheretherketone fiber, and then mixed with nitric acid and sulfuric acid after drying, stirred and washed to neutrality, and then mixed with stannous chloride and hydrochloric acid after drying, stirred and dried to obtain pretreated polyetheretherketone fiber; The silane coupling agent, ethanol and water are mixed to obtain a silane coupling agent solution, and the pretreated polyetheretherketone fiber is immersed in the silane coupling agent solution, and then dried after immersion to obtain the silane-modified polyetheretherketone fiber.
6. The organic composite phenolic resin material according to claim 5, characterized in that: The mass ratio between the polyetheretherketone fiber and the silane coupling agent is 1:(0.08-0.12).
7. The organic composite phenolic resin material according to claim 4, characterized in that: The modified graphene oxide comprises graphene oxide and meta-phenylenediamine.
8. The organic composite phenolic resin material according to claim 7, characterized in that: The modified graphene oxide is prepared by the following method: The graphene oxide and m-phenylenediamine are dispersed and mixed with deionized water, and stirred for reaction after ultrasonic treatment. After the reaction, the mixture is filtered and freeze-dried to obtain the modified graphene oxide.
9. The organic composite phenolic resin material according to claim 4, characterized in that: The mass ratio between the silane-modified polyetheretherketone fiber and the modified graphene oxide is (4.2-4.6):
1.
10. A method for preparing the organic composite phenolic resin material according to claim 1, characterized in that: The steps include: The modified phenolic resin matrix and the polyetheretherketone fiber composite material are mixed, and a curing agent is added after stirring, and the stirring is continued, and then the mixture is cured to obtain an organic composite phenolic resin material.